Targeted Next-Generation Sequencing Indicates a Frequent Oligogenic Involvement in Primary Ovarian Insufficiency Onset - Rossetti, Raffaella; Moleri, Silvia; Guizzardi, Fabiana; Gentilini, Davide; Libera, Laura; Marozzi, Anna; Moretti, Costanzo; Brancati, Francesco; Bonomi, Marco; Persani, Luca (Frontiers in Endocrinology, 2021)
Primary Ovarian Insufficiency (POI) is one of the major causes of female infertility associated with the premature loss of ovarian function in about 3.7% of women before the age of 40. This disorder is highly heterogeneous and can manifests with a wide range of clinical phenotypes, ranging from ovarian dysgenesis and primary amenorrhea to post-pubertal secondary amenorrhea, with elevated serum gonadotropins and hypoestrogenism. The ovarian defect still remains idiopathic in some cases; however, a strong genetic component has been demonstrated by the Next-Generation Sequencing (NGS) approach of familiar and sporadic POI cases. As recent evidence suggested an oligogenic architecture for POI, we developed a target NGS panel with 295 genes including known candidates and novel genetic determinants potentially involved in POI pathogenesis. Sixty-four patients with early onset POI (range: 10-25 years) of our cohort have been screened with the 90% of target coverage at 50X. Here, we report 48 analyzed patients with at least one genetic variant (75%) in the selected candidate genes. In particular, we found: 11/64 patients (17%) with 2 variants; 9/64 (14%) with 3 variants; 9/64 (14%) with 4 variants; 3/64 (5%) with 5 variants and 2/64 (3%) with 6 variants. The most severe phenotypes were associated with either the major number of variations or a worse prediction in pathogenicity of variants. Bioinformatic gene ontology analysis identified the following major pathways likely affected by genes variants: 1) Cell cycle, Meiosis and DNA repair; 2) Extracellular Matrix remodeling; 3) Reproduction; 4) Cell metabolism; 5) Cell proliferation; 6) Calcium homeostasis; 7) NOTCH signaling; 8) Signal transduction; 9) WNT signaling; 10) Cell death; and 11) ubiquitin modifications. Consistently, the identified pathways have been described in other studies dissecting the mechanisms of folliculogenesis in animal models of altered fertility. In conclusion, our results contribute to define POI as an oligogenic disease and suggest novel candidates to be investigated in patients with POI.